Tourism and English day policy in East Nusa Tenggara Province: the attitude of civil servants (ASN: Aparatur Sipil Negara) - Toni, Elvis Albertus Bin; Hornay, Priscilla Maria Assis; Djehatu, Maria Goreti; Danibao, Bernardus Kopong; Cacciafoco, Francesco Perono; Wu, Shiyue (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study examines the attitudes of East Nusa Tenggara (NTT) civil servants toward the English Day Policy introduced in Governor Regulation No. 56 of 2018. The policy aligns with NTT’s focus on tourism development, emphasizing English proficiency as key to enhancing global competitiveness. Addressing a research gap, the study explores the sociolinguistic effects of promoting English in a multilingual, culturally rich region. Data were collected from 604 civil servants via an online questionnaire distributed through WhatsApp. The survey included seven Likert-scale statements and one open-ended question in Bahasa Indonesia. Using a mixed-method approach, the analysis combined quantitative data with qualitative sociolinguistic insights. Findings reveal generally positive attitudes toward the policy, with most respondents agreeing that English is crucial for tourism and acknowledging the policy’s benefits. They also dismissed concerns that the initiative could harm local languages or Bahasa Indonesia. However, participants noted limitations in implementing the language policy, highlighting that favorable attitude alone cannot ensure its success.